Safflower genotypes submitted to soil density levels - Bonfim-Silva, Edna Maria; Paludo, Juliana Tertezinha Sasso; Silva, Tonny José Araújo da; Fenner, William; Zanotto, Maurício Dutra (Comunicata Scientiae, 2018)
It is essential to have knowledge of changes in soil structure, as a result of agricultural use and its relationship with crop development, especially those with potential for use in new regions, such as the cultivation of safflower (Carthamus tinctorius L.) in the Cerrado. In view of this dynamics, the objective was to evaluate the phytometric components of safflower genotypes submitted to levels of soil densities in Cerrado Oxisol. Ten safflower genotypes were then submitted to compaction (five densities: 1.0, 1, 2, 1.4, and 1.8 Mg m-3) in a completely randomized design with four replications under greenhouse conditions. The plots consisted of an overlap of three rings of polyvinylidene chloride of 0.01 m height each, and the treatments were applied in the intermediate layer. The phytometric components (plant height, number of leaves and stem diameter) and shoot dry mass of the crop were evaluated at 30, 60 and 90 days after sowing. There was no significant interaction between safflower genotypes and soil densities, with the effects being isolated for genotypes and/or densities when significant. For the phytometric characteristics evaluated, the genotypes PI250196, PI301049, PI305173, and PI305205 are more stable about the variations of soil density in comparison to the others. The phytometric components and dry mass of safflower shoot are impaired from the mean density of 1.2 Mg m-3.